Steady-state and Dynamic Characteristics ofWater-lubricated Rubber Bearings under Two Sets of Reynolds Boundary Conditions - Liu, Gang; Li, Ming (Discontinuity, Nonlinearity, and Complexity, 2026)
The lubrication characteristics of bearings are significantly influenced by boundary conditions. The double Reynolds boundary conditions (DRBCs) are introduced to analyze the hydrodynamic lubrication characteristics of water-lubricated rubber bearings for turbulent flows, considering the elasticity of rubber liner. Differences in its steady state and dynamic characteristics arising from the DRBCs and the Reynolds boundary conditions (RBCs) are discussed based on the finite difference method. The results show that the water-film reformation boundary is significantly different between the two sets of conditions, however, the load capacity of the bearing is only slightly different. The attitude angle and friction are greater for DRBCs than for RBCs. In the horizontal direction, direct stiffness and direct damping coefficients are larger for DRBCs than for RBCs, but in the vertical direction the opposite result holds.